HUBUNGAN TINGKAT PENGETAHUAN PERAWAT TENTANG KANKER SERVIK DENGAN TINGKAT MOTIVASI UNTUK PAPSMEAR DI RUMAH SAKIT BAPTIS KEDIRI - Wulandari, Riris (Jurnal Penelitian STIKES Kediri, 2010)
Background :There is servical cancer which attack nurse make a motivation to nurse to do papsmear. Nurse’s knowledge about cervical cancer could give an influence motivation to papsmear. The purpose of this study was to know correlation of degree of nurse’s knowledge about cervical cancer with degree of motivation to papsmear in Kediri Baptist Hospital. Method : This research was correlational design.Total sample was 69 respondent using purposive sampling.. The independent variables were degree of nurse’s knowledge  about cervical cancer. The dependent variables was degree of motivation to papsmear.Then analized using Spearman Rho with significant range 0,05. The Result of this study indicated most of nurse has good knowledge that there 46 respondent ( 67 % ) and most of nurse has good motivation to papsmear that there were 54 respondent ( 78 % ) with significant range ( p ) : 0,000. Conclusion : The conclusion of this reserch was degree of nurse’s knowledge about cervical cancer has correlation with degree of motivation to papsmear, because p £ 0,05. Further studies should involve larger respondents and better measurement tools to obtainmore accurate results.